Texture and colour characteristics, and optimisation of sodium chloride, potassium chloride and glycine of reduced-sodium frankfurter - Chartchai Wilailux (2020)
© 2019 Institute of Food Science and Technology The three-components mixture design was applied to optimise a ratio of NaCl (0%–65%), KCl (35%–100%) and glycine (0%–20%) in reduced-sodium frankfurters. Fourteen frankfurters were analysed for texture and colour, and consumer (n = 100) acceptability. Results indicated that NaCl levels affected consumer acceptability of reduced-sodium frankfurters. Increasing NaCl generally increased texture hardness. Optimisation of a salt mixture was performed by superimposing contour plots of predicted acceptability scores (≥5.5 on a 9-points hedonic scale) of all sensory attributes and revealed the optimal salt mixture: 40.03%–63.66% NaCl, 35.00%–55.90% KCl and 0.00%–20.00% glycine. The optimal salt mixture contained 220–340 mg Na/100g frankfurter compared with 540 mg Na/100 g of the control formulation (100% NaCl). The mean overall liking score (5.9 vs. 5.9) of the optimal reduced-sodium frankfurter was not different from the control (100% NaCl). This optimal formulation had >25% sodium reduction and could be claimed as ‘reduced-sodium’ according to US Food and Drugs Administration regulation.